A study: user interface design of social network for elderly generation-Y focusing on Skype video call using smart TV / Shahrul Bariah Abd Rahim - Abd Rahim, Shahrul Bariah (2014)
Social network has been adopted successfully as communication medium by Generation-Y in Malaysia. However the present elderly did not find social network as part of their lifestyle. The reason may be due to the different of users' experience and different interest. Hence today elderly users find it is less effective for them to use social media. Due to this reason, studies on user interface design for elderly focusing social network area is required in order to sustain the interest and support the Generation- Y needs when they aging and become elderly users. The aim of this research is to investigate the usage pattern of video call application on social network and to suggest the design features for elderly users. It is hope this research will enable the Generation-Y to continue enjoying their communication experience and engagement through social network as they grow and become elderly user in the next future. This research will be an instrument to examine the usage pattern of video call for Generation-Y. In order to support Generation-Y future needs, this research also investigates the most effective user interface design for video call on social network. It is hope that from this study, a propose guideline of features for video call application that focus on elderly users based on user experience will be able to produce. The propose guideline highlight user interface features for the video call application that focus on elderly users' need.